On a Foundation Wide in Scope: the History of Mount Sinai Hospital, Milwaukee, Wisconsin 1903-1987 - (:unkn) unknown (My University, 2016)
This research studies the history of Mount Sinai Hospital in Milwaukee, Wisconsin, a private, nonsectarian Jewish hospital. It was supported by the Jewish residents in Milwaukee through their philanthropic efforts for eighty-three years. In 1987, the hospital merged with a Christian hospital, but in 1992, hospital administrators announced that the establishment of operational practices designed to maintain the Jewish identity of the current hospital. I sought to answer the question of why a Jewish identity mattered to the new hospital after the merger. This research reveals that the Jewish identity of Mount Sinai came from the strong Jewish support in the early years, not from a large Jewish population, strict religious practices, or a majority of Jewish patients. I argue that the hospital represented a sense of collective action between two conflicted groups within the Jewish population of Milwaukee. These groups were divided along socioeconomic class and ethnic differences. The hospital provided a communal place for all Jewish residents to perform acts of charity, including fundraising and volunteer work. I argue the relationship between the Jewish population and the hospital was symbiotic, in that the hospital provided opportunities for Jewish doctors to establish practices and also provided economic opportunities and gave the Jewish population an icon for their charity efforts. I argue that the hospital historically treated more Gentiles than Jewish patients, but was a Jewish hospital by way of the Jewish collective action and support. I argue that the collective action of Milwaukee Jewish residents gave Mount Sinai a Jewish identity. However, changes in funding options for indigent care decreased the Jewish presence at Mount Sinai. It decreased as the need for fundraising for direct patient care decreased. After the creation of Medicaid and the expansion of Medicare, the direct financial support and the volunteer hours donated to Mount Sinai by Jewish residents decreased. As more affluent members of the Milwaukee Jewish population moved away, the Jewish participation at Mount Sinai diminished. I argue that the announcement about establishing a Jewish identity at the former Mount Sinai in 1992 represented an attempt to preserve the history of the traditional Jewish presence at the and to remind the residents of Milwaukee of the contributions of the Jewish people.
Keywords: History of Health Care for the Poor; Milwaukee Jewish Immigration; Nonsectarian Jewish Hospitals